Interest rate risk and monetary policy normalisation in the euro area - Philip Molyneux; Livia Pancotto; Alessio Reghezza; Costanza Rodriguez D'Acri (European Central Bank (ECB), 2020)
In the current low interest rate environment in the euro area there is potential for a sudden increase in interest rates and heightened interest rate risk (IRR). By using a sample of 81 euro area banks during the period 2014Q4-2018Q1 and a confidential supervisory measure of IRR, this paper identifies which bank-specific characteristics can amplify or weaken the impact of a 200 basis points positive shock in interest rates. We find that banks reliant on core deposits, that hold more floating-interest rate loans and that diversify their lending, either by sector or geography, are less exposed to a positive change in interest rates. Interestingly, we discover that banks that did not exploit the exceptional financing provided by the European Central Bank (ECB) reveal greater IRR exposure. These findings advance the debate on the impact on euro area banking of a possible return to a normalised monetary policy.
Keywords: E43; E44; E52; G21; F44; 330; Interest Rate Risk; Low Interest Rate Environment; Balance-sheet determinants; Unconventional Monetary Policies